Effect of silicone resin on the properties of silica ceramic cores by heating treatment. Issue 24 (16th December 2016) - Yang, Zhigang; Yu, Jianbo; Li, Chuanjun; Deng, Kang; Ren, Zhongming
Abstract: Silica ceramic cores prepared by heat-press molding were strengthened by impregnating silicone resin. The effect of heating treatment conditions on the properties of silica ceramic cores was analyzed. Results showed that the ambient bending strength increased from 9.3 ± 2.0 MPa to 24.8 ± 1.5 MPa by curing process at low temperature of 250 °C. However, further heating treatment at high temperature ranging from 1150 to 1300 °C made the strength of the samples lower than that of the cured samples owing to the decomposition of silicone resin. But the strength of the samples was still higher than that of raw samples. The increasing heating treatment temperature promoted an increase in the strength by a densification process.